DNA barcoding highlights a cryptic species of grenadier Macrourus in the Southern Ocean - Smith, P. J. (2011)
Although three species of the genus Macrourus are recognized in the Southern Ocean, DNA sequencing of the mitochondrial COI gene revealed four well-supported clades. These barcode data suggest the presence of an undescribed species, a conclusion supported by meristic and morphometric examination of specimens.